2015
DOI: 10.1016/j.neuron.2014.12.053
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Activity in Primate Dorsal Anterior Cingulate Cortex Signals Task Conflict and Predicts Adjustments in Pupil-Linked Arousal

Abstract: Summary Whether driving a car, shopping for food, or paying attention in a classroom of boisterous teenagers, it’s often hard to maintain focus on goals in the face of distraction. Brain imaging studies in humans implicate the dorsal anterior cingulate cortex (dACC) in regulating the conflict between goals and distractors. Here we show for the first time that single dACC neurons signal conflict between task goals and distractors in the rhesus macaque, particularly for biologically-relevant social stimuli. For … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
165
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(182 citation statements)
references
References 65 publications
17
165
0
Order By: Relevance
“…One possibility is that outcome may depend on spontaneous fluctuations in attentional preparation linked to tonic activity in the locus coeruleus, as suggested by recent pupillometry studies in macaques (Ebitz, Pearson, & Platt, 2014;Ebitz & Platt, 2015) and in humans (Braem, Coenen, Bombeke, van Bochove, & Notebaert, 2015;Gilzenrat, Nieuwenhuis, Jepma, & Cohen, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is that outcome may depend on spontaneous fluctuations in attentional preparation linked to tonic activity in the locus coeruleus, as suggested by recent pupillometry studies in macaques (Ebitz, Pearson, & Platt, 2014;Ebitz & Platt, 2015) and in humans (Braem, Coenen, Bombeke, van Bochove, & Notebaert, 2015;Gilzenrat, Nieuwenhuis, Jepma, & Cohen, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Spontaneous pupil dilations during rest have already been linked to ACC activity in the macaque monkey (Aston-Jones & Cohen, 2005;Ebitz & Platt, 2015;Joshi et al, 2016) and also to activity in dACC in humans (Murphy et al, 2014;Schneider et al, 2016). Moreover, other autonomous responses to fear stimuli have previously been related to dACC activity: the difference in SCR to CS+ and CS-in fear conditioning (Milad et al, 2007), as well as the magnitude of SCR in the anticipation of pain (Seifert et al, 2013) were found to positively correlate with dACC activity.…”
Section: Fear Conditioningmentioning
confidence: 94%
“…The interpretation of autonomic outputs, however, remains controversial (2). Inferred internal states and associated behavioral consequences vary among studies and have included veracity (2, 3), valence (4), reward (5, 6), surprise (7), attention (8), vigilance (9), arousal (10, 11), anxiety (12, 13), impulse control and emotional clarity (14), and cognitive performance (15–18). Some of these states have been grouped into the regulation and expression of emotion (1921).…”
Section: Introductionmentioning
confidence: 99%